Somatotopic organization of central arbors from nociceptive afferents develops independently of their intact peripheral target innervation. Issue 18 (30th October 2018) - Olson, William; Luo, Wenqin
Abstract: Functionally important regions of sensory maps are overrepresented in the sensory pathways and cortex, but the underlying developmental mechanisms are not clear. In the spinal cord dorsal horn (DH), we recently showed that paw innervating Mrgprd + nonpeptidergic nociceptors display distinctive central arbor morphologies that well correlate with increased synapse transmission efficiency and heightened sensitivity of distal limb skin. Given that peripheral and central arbor formation of Mrgprd + neurons co‐occurs around the time of birth, we tested whether peripheral cues from different skin areas and/or postnatal reorganization mechanisms could instruct this somatotopic difference among central arbors. We found that, while terminal outgrowth/refinement occurs during early postnatal development in both the skin and the DH, postnatal refinement of central terminals precedes that of peripheral terminals. Furthermore, we used single‐cell ablation of Ret to genetically disrupt epidermal innervation of Mrgprd + neurons and revealed that the somatotopic difference among their central arbors was unaffected by this manipulation. Finally, we saw that region‐specific Mrgprd + central terminal arbors are present from the earliest postnatal stages, before skin terminals are evident. In summary, we find that region‐specific organization of Mrgprd + neuron central arbors is present shortly after initial central terminal formation, which likely develops independently of peripheral target innervation. Our data suggest that either cell‐intrinsic and/or DH prepatterning mechanisms are likely to establish this somatotopic difference. Abstract : Somatotopic organization of a major class of mammalian nociceptors is evident at early postnatal stages. We performed sparse genetic tracing of Mrgprd+ nociceptor axonal arbors in P3 mouse spinal cords. The presence of region‐specific morphologies at early stages of spinal cord innervation suggests that pre‐patterning mechanisms could establish these differences.